HUBUNGAN ANTARA KEGIATAN EKSTRAKURIKULER BELA DIRI WUSHU SANDA DENGAN MINAT BELAJAR SISWA PADA MAPEL PJOK KELAS X.E3 SMA SWASTA BERSAMA BERASTAGI TAHUN AJARAN 2025/2026 - Daniel Frengky Sudodo Ginting; Julius Boy Nesra Basgimata Barus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between the extracurricular martial arts activity Wushu Sanda and students' learning interest in Physical Education, Sports, and Health (PJOK) in grade X.E3 at SMA Swasta Bersama Berastagi in the 2025/2026 academic year. This research used a quantitative approach with descriptive correlational method. The population was 20 students who participated in Wushu Sanda extracurricular activity, and all of them were taken as samples using total sampling technique. Data were collected through observation, interviews, and questionnaires, then analyzed using validity test, reliability test, normality test, linearity test, and Pearson Product Moment correlation with IBM SPSS Statistics 25. The results showed that the instrument was valid and reliable with Cronbach’s Alpha value of 0.963. Data were normally distributed with significance value of 0.200 (> 0.05). Correlation test obtained coefficient of 0.709 with significance value of 0.000 (< 0.05). This indicates there is a positive and significant relationship between Wushu Sanda activity and students' learning interest in PJOK subject. The higher the students' involvement in the activity, the higher their learning interest.